First Person View on Flying Robot For Real Time Monitoring - Huda Ubaya; Muhammad Iqbal (ICON-CSE, 2014)
Radio control nowadays not only control the car but can control the copter. First Person View is a way to change the viewpoint of the controller looks like in the copter. By using radio telemetry communication that sends video data from the camera on the copter and will be shown on a display on ground station. Radio telemetry communication will use wideband modulation techniques to transmit video at high speed until the video is shown to be a real time video. The transmitter has been designed which is able to transmit video data up to 1 kilometers. Good quality video data can be sent about 500 meters below. measurement of Peak Signal to Noise Ratio (PSNR) that distance and wall are greatly affect the quality of the video. Deficiencies in the delivery of video communication can be minimized by increasing the gain and transmission power of the radio frequency telemetry and matching between the video telemetry radio and radio control copter.